ANALISIS KESULITAN MEMBACA PADA SISWA KELAS IIIA SDN PENGARON 2 - Devia Novrisalianti; Wulida Makhtuna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the fact that several third-grade students of class IIIA at SDN Pengaron 2 still experience reading difficulties, characterized by their inability to read fluently, errors in pronouncing words, and difficulties in understanding the content of simple texts, which affect the learning process. This study aims to analyze the forms of reading difficulties, identify the factors causing these difficulties, and describe teachers’ efforts in overcoming reading difficulties among students in class IIIA at SDN Pengaron 2. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of three students who experienced reading difficulties and one third-grade teacher. Data were collected through observation and interviews, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, with validity testing conducted through triangulation. The results showed that students experienced difficulties in recognizing and pronouncing words, reading fluently, understanding reading content, and using punctuation and intonation appropriately. These difficulties were influenced by internal factors, including low interest and motivation in reading, and external factors, including limited reading practice at home and inadequate support from the learning environment. Teachers addressed these difficulties through individual reading guidance, repeated reading exercises, and assistance tailored to students’ abilities. It is concluded that addressing reading difficulties requires collaboration among teachers, parents, and the learning environment to support the improvement of students’ reading abilities.